The Correlation Between Students' Listening Comprehension and Their Perception of Listening Teaching Materials - Alifah, Zakia Putri; Trisno, Edi (Universitas Negeri Padang, 2024)
The most significant problems with students' listening include difficulties comprehending accents, speaking speed, and limited vocabulary. Teaching materials that are relevant to student's interests might help them comprehend listening more effectively, as seen by their perceptions. This research aims to find out the correlation between students' listening comprehension and their perceptions of listening teaching materials. The sample consisted of 52 students from the Department of English Education at Padang State University in 2022 who had completed advanced listening courses and were chosen using cluster random sampling. The study instrument comprises the final exam score and questionnaire findings, which were analyzed using SPSS 25 for Windows and Pearson Product Moments. The findings reveal a sign (2-tailed) of 0.18 < 0.05, showing a significant correlation between the variables. As a result, these findings show a positive relationship between students' listening comprehension and their perception of listening teaching materials. This research highlights the need for a multifaceted approach in designing listening teaching materials and the importance of considering factors such as students' motivation, interest, and the overall quality of teaching to maximize listening comprehension and general teaching effectiveness. The implications of these findings reinforce the urgency to develop holistic learning approaches to improve the effectiveness of language teaching.